Single-Dose Lignocaine-Based Blood Cardioplegia in Single Valve Replacement Patients - Ramani,Jaydip (2017)
Abstract OBJECTIVE: Myocardial protection is the most important in cardiac surgery. We compared our modified single-dose long-acting lignocaine-based blood cardioplegia with short-acting St Thomas 1 blood cardioplegia in patients undergoing single valve replacement. METHODS: A total of 110 patients who underwent single (aortic or mitral) valve replacement surgery were enrolled. Patients were divided in two groups based on the cardioplegia solution used. In group 1 (56 patients), long-acting lignocaine based-blood cardioplegia solution was administered as a single dose while in group 2 (54 patients), standard St Thomas IB (short-acting blood-based cardioplegia solution) was administered and repeated every 20 minutes. All the patients were compared for preoperative baseline parameters, intraoperative and all the postoperative parameters. RESULTS: We did not find any statistically significant difference in preoperative baseline parameters. Cardiopulmonary bypass time were 73.8±16.5 and 76.4±16.9 minutes (P=0.43) and cross clamp time were 58.9±10.3 and 66.3±11.2 minutes (P=0.23) in group 1 and group 2, respectively. Mean of maximum inotrope score was 6.3±2.52 and 6.1±2.13 (P=0.65) in group 1 and group 2, respectively. We also did not find any statistically significant difference in creatine-phosphokinase-MB (CPK-MB), Troponin-I levels, lactate level and cardiac functions postoperatively. CONCLUSION: This study proves the safety and efficacy of long-acting lignocaine-based single-dose blood cardioplegia compared to the standard short-acting multi-dose blood cardioplegia in patients requiring the single valve replacement. Further studies need to be undertaken to establish this non-inferiority in situations of complex cardiac procedures especially in compromised patients.